Evaluation of YouTube laparoscopic hysterectomy videos as educational materials during the COVID-19 era using the LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS) and LAP-VEGaS video assessment tool. (4th July 2022) - Unal, Fehmi; Atakul, Nil; Turan, Hasan; Yaman Ruhi, Irem
Abstract: With increasing numbers of laparoscopic hysterectomies, surgical trainees are compelled to learn more about endoscopy. Owing to coronavirus disease-related social distancing requirements, online education has gained prominence. Here, we aimed to investigate the laparoscopic hysterectomy video quality on YouTube using the LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS). YouTube was searched on June 7, 2020 using 'laparoscopic hysterectomy'. Three examiners evaluated videos using Global Operative Assessment of Laparoscopic Skills (GOALS). Subsequently, videos were assessed for their conformity to the LAP-VEGaS and LAP-VEGaS Video Assessment Tool. Interobserver reliability was estimated using intraclass coefficients and Cronbach's alpha. Cochran's Q test was used to determine correlations among quantitative data. The median GOALS score was 21.50. The observers' GOALS scores were significantly correlated. The results showed low conformity to the LAP-VEGaS. YouTube is the most used platform among trainees. The low YouTube video educational quality highlights the necessity for peer review, as trainees increasingly seek such resources during the pandemic. IMPACT STATEMENT: What is already known on this subject? YouTube is the most commonly used online resource for educational material among surgical trainees. Online videos usually do not undergo a peer-review process. The LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS) may be used to assess the educational quality of surgical videos. What do the results of this study add? To our knowledge, this is the first study on the quality of laparoscopic hysterectomy videos available on YouTube and the first study to evaluate YouTube laparoscopic surgery videos using the LAP-VEGaS Video Assessment Tool (VAT). Our study revealed the low educational quality of YouTube laparoscopic hysterectomy videos. The LAP-VEGaS VAT seems to be a valid and practical tool for assessing online laparoscopic hysterectomy videos. What are the implications of these findings for clinical practice and/or further research? Medical communities, especially tertiary care or academic centres, may upload educational peer-reviewed videos for trainees seeking this type of resource, especially during the coronavirus disease pandemic, as surgical education alternatives are limited.